Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12529-015-9468-0
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status, Waist-to-Hip Ratio, and Short-Term Heart Rate Variability in Cambodians with Type 2 Diabetes

Abstract: Central adiposity shows a stronger deleterious association with autonomic tone among individuals with more adverse social conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Previous work has shown that social adversity is related to lower HRV. This includes racial minority status, social class, cumulative life stress ( 22 ), and poverty ( 23 ). Yet, here we show that even among minorities of low socioeconomic status, diabetes-specific FI exerts a unique effect on HRV above and beyond other socioeconomic stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that social adversity is related to lower HRV. This includes racial minority status, social class, cumulative life stress ( 22 ), and poverty ( 23 ). Yet, here we show that even among minorities of low socioeconomic status, diabetes-specific FI exerts a unique effect on HRV above and beyond other socioeconomic stressors.…”
Section: Discussionmentioning
confidence: 99%